Ruído e incômodo em uma população de bombeiros do município de Santo André-SP - Guzman, Michelle Barna (2007)
Objective: Identify complaints related to the auditory health and annoyance caused by occupational and urban noises, in a firefighters corporation from Santo André county, and carry out a sound mapping from the surrounding area. Methods: A cross-sectional study was concerned in a population of 72 firefighters from the 8th brigade, being 28 from the administrative section, 20 from the occurrence center and 24 from the operational call center, using a protocol which consisted of 57 questions about personal data, auditory complaints, non-auditory complaints and annoyance. A sound mapping from the surrounding area was performed. Results: The sound pressure levels in the firefighter corporation area exceeded 67 dB (A), reaching more than 82 dB (A) in the avenue. Evaluating 72 firefighters, 95,8% are male. More than half (59,7%) have high school level. Most of them (83,3%) reported noisy work in their everyday life, being the urban noise reported as the major problem. When evaluated separately by performance section, the highest occurrence is urban noise (73,9%), firefighter vehicle noise (68,0%) and telephone noise (38,2%), in the administrative section, operational call center and occurrence center, respectively. The noisiest periods were in the morning and afternoon (45,5%), interfering in work activities for 65% of the interviewed. The most mentioned alterations were concentration (43,4%) and hearing (26,4%). Related to the hearing perception, most of them (55,6%) reported good hearing. When it comes to chemical exposure products, 55,6% reported exposure during work activities. Conclusions: Interviewed firefighters, besides noisy exposure deriving from work activities, like vehicles, walk-talk radios and telephones, are liable to consequences from the urban noise, which disturbs work activities and also causes health problems